IMPROVING STUDENTS' VOCABULARY MASTERY THROUGH ENGLISH SONGS AT THE EIGHTH GRADE OF SMP - Blessy Monique Wilar; Nurmin F Samola; Agustine C Mamentu (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The objective of this research is to discover the effectiveness of using songs in improving students’ vocabulary mastery. This research is conducted at the eighth grade students of SMP Negeri 7 Manado in the academic year of 2020-2021. There are 20 students engaged to be the subject of this study. The researchers select one class to get treatment in order to achieve the objective of this study. The data are obtained through pre-test and post-test. Before giving the treatment to the students, the researchers firstly measure their knowledge by giving a pre-test. Then after doing the treatment, the students are required to do a post-test to find out whether the treatment has a significant effect on students’ vocabulary mastery or not. Memorizing songs can be utilized in English learning to improve students’ vocabulary mastery. Thus, the learning objectives can be reached successfully. Improving vocabulary mastery using songs is not only beneficial but also pleasant for students. They become more interested in studying and not easy to get bored. The relationship between teachers and students also becomes closer because students tend to feel more comfortable asking questions to their teachers about the difficulties or new words they find. It can be seen from the students’ scores in post-test that are higher than the pre-test. The average score of the pre-test is 3,85 and the average score of the post-test is 12,65. Finally, the researchers conclude that songs give a significant impact in improving students’ vocabulary mastery.